PERILAKU AMAN BERKENDARA PENGEMUDI TRUK TANGKI BBM (STUDI KUALITATIF DI PERUSAHAAN DISTRIBUSI BBM PT X KOTA SEMARANG) - Syifa Awalia Rahma; Bina Kurniawan; Siswi Jayanti (Jurnal Kesehatan Masyarakat (Undip), 2017)
Safe driving behavior helps to avoid traffic problems. Safety driving can be influence by several factors such as the predisposing factor, the enabling factor, and the reinforcing factor. Safety driving is the basic of further driving training that care more about safety for drivers and passengers. PT X is the authorized agent of PT. Pertamina (Persero) to sell and distribute non-subsidize fuel for the industrial sector and others. The aim of this study was to describe the safe behavior of the driver of fuel tanker truck PT X. This was a qualitative descriptive research and conducted in June 2017. The main informant in this study were five tanker driver who had a history of accidents and the triangulation informant was operational manager and head driver who are responsible in the operational activities of the distribution of fuel. The result showed that drivers have a good knowledge of safe driving behavior. The driver showed a positive attitude about implementing safe driving behavior. Drivers agreed that with the rules and safety-driving training will establish safe behavior in driving. The supervisory role of superiors was not likely to affect the safe behavior of tanker truck drivers but the role of colleagues and families has a positive effect. Therefore, suggestions for the company are to compile SOP, conduct safety driving training, and make supervision program while driving so that the driving behavior of all drivers of PT X becomes good.